Psychosis in Patients with Narcolepsy as an Adverse Effect of Sodium Oxybate - Sarkanen, Tomi; Niemelä, Valter; Landtblom, Anne-Marie; Partinen, Markku (Frontiers in Neurology, 2014)
Aim: Hypnagogic and hypnopompic hallucinations are characteristic symptoms of narcolepsy, as are excessive daytime sleepiness, cataplexy and sleep paralysis. Narcolepsy patients may also experience daytime hallucinations unrelated to sleep-wake transitions. The effect of medication on hallucinations is of interest since treatment of narcolepsy may provoke psychotic symptoms. We aim to analyze the relation between sodium oxybate (SXB) treatment and psychotic symptoms in narcolepsy patients. Furthermore, we analyze the characteristics of hallucinations to determine their nature as mainly psychotic or hypnagogic and raise a discussion about whether SXB causes psychosis or if psychosis occurs as an endogenous complication in narcolepsy. Method: We present altogether four patients with narcolepsy who experienced psychotic symptoms during treatment with SXB. In addition, we searched the literature for descriptions of hallucinations in narcolepsy and similarities and differences with psychotic symptoms in schizophrenia. Results: Three out of four patients had hallucinations typical for psychosis and one had symptoms that resembled aggravated hypnagogic hallucinations. Two patients also had delusional symptoms primarily associated with mental disorders. Tapering down SXB was tried and helped in two out of four cases. Adding antipsychotic treatment (risperidone) alleviated psychotic symptoms in two cases. Conclusion: Psychotic symptoms in narcolepsy may appear during SXB treatment. Hallucinations resemble those seen in schizophrenia however the insight that symptoms are delusional is usually preserved. In case of SXB-induced psychotic symptoms or hallucinations, reducing SXB dose or adding antipsychotic medication can be tried.